2021
DOI: 10.1017/jgc.2021.25
|View full text |Cite
|
Sign up to set email alerts
|

Positive youth development: A brief review of literature with implications for school-based psychological interventions

Abstract: There is a recognition about the mental health, educational, and career-related benefits of positive youth development (PYD) in children and youth. This brief review provides an overview of the current application of PYD in school settings. We begin by summarising the common conceptualisations of PYD along with similar and distinct features in such models. Then, we discuss the current status of PYD research and highlight the academic and psychological payoffs of PYD-oriented programs in schools. Importantly, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 54 publications
(95 reference statements)
0
6
0
Order By: Relevance
“…Although past studies have confirmed the factor structure of the Five Cs model among early, middle, and late adolescents (Geldhof et al, 2014) as well as its expected associations with positive (e.g., academic achievement, life satisfaction, pro-social behaviors) and negative developmental outcomes (e.g., symptoms of anxiety and depression, risk-taking behaviors; Buenconsejo & Datu, 2021;Lerner et al, 2005), scarce investigations have examined personal and organizational antecedents and interactions that may foster greater PYD characteristics, particularly in non-Western and collectivistic societies such as the Philippines. In this study, we propose adolescent religiosity (i.e., participation in a faith-based organization or community; Koenig & Büssing, 2010) and spirituality (i.e., personal sense of transcendence or relationship with something greater than the self; King et al, 2017) as psychological resources that can facilitate Filipino adolescents' PYD characteristics.…”
Section: The Five Cs Of Positive Youth Developmentmentioning
confidence: 98%
See 2 more Smart Citations
“…Although past studies have confirmed the factor structure of the Five Cs model among early, middle, and late adolescents (Geldhof et al, 2014) as well as its expected associations with positive (e.g., academic achievement, life satisfaction, pro-social behaviors) and negative developmental outcomes (e.g., symptoms of anxiety and depression, risk-taking behaviors; Buenconsejo & Datu, 2021;Lerner et al, 2005), scarce investigations have examined personal and organizational antecedents and interactions that may foster greater PYD characteristics, particularly in non-Western and collectivistic societies such as the Philippines. In this study, we propose adolescent religiosity (i.e., participation in a faith-based organization or community; Koenig & Büssing, 2010) and spirituality (i.e., personal sense of transcendence or relationship with something greater than the self; King et al, 2017) as psychological resources that can facilitate Filipino adolescents' PYD characteristics.…”
Section: The Five Cs Of Positive Youth Developmentmentioning
confidence: 98%
“…More recently, developmental scientists have concentrated on positive youth development (PYD) as an alternative perspective to study the second decade of life by emphasizing young people's strengths as well as their capacity to thrive in their respective ecologies (Benson et al, 2006; Lerner et al, 2010). There are several models and frameworks that attempt to conceptualize and measure PYD and its dimensions (see Buenconsejo & Datu, 2021, 2022). One of which is the Five Cs model, which characterizes adolescent thriving in terms of five interrelated but distinct constructs: competence , confidence , connection , character , and caring (Lerner et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As PYD gained increasing traction from researchers and practitioners, the number of frameworks that conceptualized adolescent thriving also multiplied from relatively simple dimensions to more complex models . Preliminary scholarship on PYD operationalized adolescent thriving has adopted unidimensional constructs such as initiative, resilience, and purpose (Buenconsejo & Datu, 2021;Burkhard et al, 2020). However, contemporary researchers have created multidimensional paradigms to characterize healthy adolescent development (Burkhard et al, 2020;.…”
Section: Theoretical Conceptualizations Of Pydmentioning
confidence: 99%
“…These frameworks have gained considerable attention among researchers and practitioners from various fields, including developmental psychology, education, medicine, public health, social work, and sociology (Lerner, 2017;Qi et al, 2020). Several PYD models have also been used to design, implement, and evaluate youth programs and interventions that aim to promote academic and psychosocial well-being in schools and socially challenged communities (Buenconsejo & Datu, 2021;.…”
mentioning
confidence: 99%